Pengaruh Metode Pembelajaran Numbered Heads Together Terhadap Hasil Belajar Siswa Pada Materi Sistem Tata Surya di Mata Pelajaran Ipa - Nurhamimah Rambe; Renni Ramadhani Lubis; Titin Rahmayanti Rambe; Wina Mariana Parinduri (LPPM STKIP AL MAKSUM, 2022)
This research is backgrounded by students' inactivity in following the lessons given by the teacher because the teacher only uses the same method in every teaching and learning activity, always uses monotonous teaching methods so as to make students bored, students lack the courage to ask questions, and some students do not complete the assigned tasks properly whose results are low student learning outcomes at SD Swasta PAB 10 Sampali. which is characterized by student learning outcomes that have not reached the minimum threshold of completeness criteria. Low student learning achievement is caused by the learning process that has not been maximized. This study aims to determine the influence of the Numbered Head Together (NHT) learning method on science subjects in improving the learning outcomes of grade IV students at SD Swasta PAB 10 Sampali. In science learning, there are several cooperative learning models that can be used to improve learning outcomes and make students active. One of them is the Numbered Heads Together (NHT) learning method. The Numbered Heads Together method is part of a structural cooperative learning model, which emphasizes specific structures designed to influence student interaction patterns.